Crystallization and preliminary X-ray crystallographic analysis of human RGS10 complexed with G alpha i3 - Lee, HK; Rhee, KH; Kim, CW; Kwang, YH; Kim, EE (INT UNION CRYSTALLOGRAPHY, 2005)
G-protein-coupled receptors, which are major targets for drug discovery, play a major role in diverse physiological processes by relating changes in the extracellular environment to intracellular functions via activation of heterotrimeric G-proteins. However, G-protein activity is also modulated by a family of proteins called regulators of G-protein signalling (RGS), which are classified into six subfamilies. RGS10 belongs to the subgroup D/R12 and is known to act specifically on activated forms of three G alpha proteins (G alpha i3, G alpha z and G alpha o but not G alpha s). It is abundantly expressed in brain and immune tissues and has been implicated in the pathophysiology of schizophrenia. The RGS domain of RGS10 was cloned, purified, complexed with human G alpha i3 and crystallized. The crystals containing both RGS and G alpha i3 belong to space group P4(3)2(1)2 ( or P4(1)2(1)2), with unit-cell parameters a = 99.88, b = 99.88, c = 144.59 angstrom, alpha = beta = gamma = 90 degrees. A full set of diffraction data were collected to 2.5 angstrom resolution at 100 K using synchrotron radiation at Pohang beamline 4A.
Keywords: PROTEIN SIGNALING RGS; REGULATORS; LOCALIZATION